Comparative analysis of modern methods for calculating product costs - N. S. Andruk; E. A. Naumova (Путеводитель предпринимателя, 2024)
The article is devoted to the analysis of methods for calculating the cost of production at an industrial enterprise. It is noted that when choosing the appropriate calculation method, along with general principles, one should take into account the specifics of the production and economic activities of each specific enterprise. For this purpose, both well–known and well–proven calculation methods, as well as modern ones used in international practice, such as «target costing» and «kaizen costing» are considered. A comparative analysis of the considered traditional and modern methods, systematized in tabular form, is provided. The advantages, disadvantages, and possible results of using each method are noted. A description of these methods is provided. Using the example of a shipbuilding enterprise, directions for improving the applied calculation methods by using the advantages of the considered methods are substantiated.